CONJUGATED FATTY ACIDS (CFAS) PRODUCTION VIA VARIOUS BACTERIAL STRAINS AND THEIR APPLICATIONS. A REVIEW - AZIZ, TARIQ; SARWAR, ABID; Daudzai, Zubaida; Din, Jalal ud; Saidal, Ahsan; Ghani, Mustajab; Khan, Ayaz Ali; Naz, Sumaira; Shahzad, Muhammad (Journal of the Chilean Chemical Society, 2022)
Conjugated fatty acids (CFAs) mainly consists of Conjugated linoleic acids (CLAs) and conjugated linolenic acids (CLNAs). CFAs received significant importance because of their anti-carcinogenic, anti-obesity, anti-diabetic, lipid/ energy metabolism modulatory effects and some other health promoting properties. Though, their concentration in food stuff is inadequate for any therapeutic application to be implemented. For a biotechnological perspective, microbial production of these CFAs has been extensively explored as an alternative and various bacterial strains of Propionbacterium, Lactobacillus and Bifidobacterium have shown promising results. This review will amass and recap available data concerning CLA and CLNA production by various bacterial strains via various enzymatic reaction behind all the processes. Numerous studies on CFA biochemical pathways are important to understand and discourse the metabolic mechanisms behind this process showing all the gene products that could be involved in the production. Among these bacterial strains few have shown the modulation of lipid metabolism in-vivo, further research should be focused on this topic which would help us to understand the role of gut microbiota on human health and future foods sustainability.